Environmental Control of Astrocyte Pathogenic Activities in CNS Inflammation - Wheeler, Michael A.; Jaronen, Merja; Covacu, Ruxandra; Zandee, Stephanie E. J.; Scalisi, Giulia; Rothhammer, Veit; Tjon, Emily C.; Chao, Chun-Cheih; Kenison, Jessica E.; Blain, Manon; Rao, Vijayaraghava T. S.; Hewson, Patrick; et al. (Cell, 2019)
An environmental trigger, the herbicide linuron boosts astrocyte pathogenic activities in the context of CNS inflammation by activating IRE1α-XBP1 signaling in mice and, potentially, multiple sclerosis patients.
CRIS-Team Scopus Importer:2020-09-22
Keywords: astrocyte; glia; inflammation; IRE1α; multiple sclerosis; neurodegeneration; Sigmar1; XBP1; zebrafish